Adult Congenital Heart Disease: A Growing Epidemic - Ávila, Pablo; Mercier, Lise-Andrée; Dore, Annie; Marcotte, François; Mongeon, François-Pierre; Ibrahim, Reda; Asgar, Anita; Miro, Joaquim; Andelfinger, Gregor; Mondésert, Blandine; de Guise, Pierre; Poirier, Nancy; et al. (Canadian journal of cardiology, 2014)
Medical and surgical breakthroughs in the care of children born with heart defects have generated a growing population of adult survivors and spawned a new subspecialty of cardiology: adult congenital heart disease. The prevalence of adult congenital heart disease is escalating at a rampant rate, outpacing the relatively static prevalence of pediatric congenital heart disease, because adults now surpass children in numbers by a ratio of 2:1. As such, congenital heart disease can no longer be considered primarily a pediatric specialty. Most congenital heart defects are not curable and require lifelong specialized care. Health care systems worldwide are challenged to meet the unique needs of this increasingly complex patient population, including the development of supraregional centres of excellence to provide comprehensive and multidisciplinary specialized care. In this review, we explore the incidence and prevalence of congenital heart disease and their changing patterns, address organization and delivery of care, highlight the importance of appropriate training and dedicated research, summarize the high burden of health care resource utilization, and provide an overview of common issues encountered in adults with congenital heart disease. Les avancées médicales et chirurgicales dans la prise en charge des enfants nés avec des malformations cardiaques ont généré un nombre croissant de survivants adultes et ont donné naissance à une nouvelle sous-spécialité de la cardiologie : la cardiopathie congénitale chez l'adulte. La prévalence des adultes atteints de cardiopathie congénitale s’amplifie à un rythme effréné, dépassant la prévalence relativement stable des cardiopathies congénitales pédiatriques, puisque les adultes dépassent maintenant en nombre les enfants avec un ratio de 2 : 1. En tant que telle, la cardiopathie congénitale ne peut plus être considérée comme étant essentiellement une spécialité pédiatrique. La plupart des anomalies cardiaques congénitales ne sont pas curables et nécessitent des soins spécialisés à vie. Les systèmes de santé du monde entier sont amenés à répondre aux besoins particuliers de cette population de patients de plus en plus complexe, y compris par le développement de centres d'excellence suprarégionaux afin de fournir des soins spécialisés d’ensemble et multidisciplinaires. Dans cette revue, nous examinons l'incidence et la prévalence des cardiopathies congénitales et leurs particularités changeantes, nous abordons l'organisation et la prestation des soins, mettons en évidence l'importance d'une formation appropriée et d’une recherche dédiée, résumons la charge considérable de l'utilisation des ressources des soins de santé, et nous fournissons un aperçu des problèmes habituels rencontrés chez les adultes atteints de cardiopathie congénitale.